2018
DOI: 10.18034/mjmbr.v5i2.456
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Hyaluronic Acid into Platelet-Rich Fibrin Lysate in Restoration of Senescent Human Dermal Fibroblasts Activities

Abstract: Senescent human dermal fibroblasts had reduced capacity in proliferation and collagen synthesis. It is due to unresponsiveness against transforming growth factor-β1 (TGF-β1) stimulation. Either platelet-rich fibrin (PRF)-lysate or hyaluronic acid (HA) can restore TGF-β1 signaling pathway. To determine whether HA addition to PRF lysate has a better activity than PRF-lysate alone in restoring senescent human dermal fibroblasts (HDFs) activities. HDF isolated from six different human skins was divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(41 reference statements)
0
4
0
Order By: Relevance
“… 21 Another study revealed that the combination of HA and PRF can increase human dermal fibroblasts activity and show better effects in combination. 22 …”
Section: Discussionmentioning
confidence: 99%
“… 21 Another study revealed that the combination of HA and PRF can increase human dermal fibroblasts activity and show better effects in combination. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Azyenela et al, proved that the addition of HA to PRF improved the ability of skin fibroblasts made senescence by the starvation method [13] . The hypothesis in this study was that by adding HA crosslinking to PRF-L, there would be an elevated GF release in PRF-L.…”
Section: Discussionmentioning
confidence: 99%
“…PRF-L sample was taken from venous blood of 1 healthy adult. PRF-L was a lysate obtained from PRF isolated from volunteer blood with 50% levels dissolved in Dulbecco's minimal essential medium (DMEM) + fetal bovine serum (FBS) 1% (Gibco™, Massachusetts, USA) [13] .…”
Section: Preparation Of Prf Lysate (Prf-l)mentioning
confidence: 99%
“…Addition of PRF to HA has been found to be an excellent candidate material for treating clinical signs of aging related to aging human dermal fibroblasts by increasing their responsiveness to transforming Growth Factor β 1 (TGF-β 1). [ 29 ] This indication needs to be further explored to increase the effectiveness of the commonly used HA fillers in aging skin.…”
Section: Use Of Prf In Dermatologymentioning
confidence: 99%